2018
DOI: 10.1080/10619127.2018.1463016
|View full text |Cite
|
Sign up to set email alerts
|

Photonuclear Reactions in Astrophysics

Abstract: Photodisintegration in stellar environmentsNucleosynthesis in stars and stellar explosions proceeds via nuclear reactions in thermalized plasmas. Nuclear reactions not only transmutate elements and their isotopes, and thus create all known elements from primordial hydrogen and helium, they also release energy to keep stars in hydrostatic equilibrium over astronomical timescales. A stellar plasma has to be hot enough to provide sufficient kinetic energy to the plasma components to overcome Coulomb barriers and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Although the p-process consists of photodisintegration reactions starting on stable seed nuclei and moving off stability to neutron-deficient nuclei, these reactions are more often better probed with the inverse charged-particle reaction measurements [262]. Nonetheless, γ-beam facilities such as HIγS can provide unique insights for special cases [263].…”
Section: How Did We Get Here?mentioning
confidence: 99%
“…Although the p-process consists of photodisintegration reactions starting on stable seed nuclei and moving off stability to neutron-deficient nuclei, these reactions are more often better probed with the inverse charged-particle reaction measurements [262]. Nonetheless, γ-beam facilities such as HIγS can provide unique insights for special cases [263].…”
Section: How Did We Get Here?mentioning
confidence: 99%
“…Although the p-process consists of photodisintegration reactions starting on stable seed nuclei and moving off stability to neutron-deficient nuclei, these reactions are more often better probed with the inverse charged-particle reaction measurements [259]. Nonetheless, γ-beam facilities such as HIγS can provide unique insights for special cases [260].…”
Section: How Did We Get Here?mentioning
confidence: 99%
“…Additionally, it has been suggested that photodisintegration experiments can also probe particle emission to excited states in the final nucleus and thus provide information on the transitions needed to calculate astrophysical capture rates [38][39][40]. This allows to better constrain the reaction models by being able to test calculations, e.g., by using different optical potentials in the computation of the relevant transitions and comparing them to the data [41].…”
Section: Introductionmentioning
confidence: 99%